Strategic Approach in Social Media Marketing and a Study on Successful Facebook Cases - Bekoglu, Filiz Bozkurt; OnaylÄ±, Cemre (European Scientific Journal, ESJ, 2016)
Development of internet and social media has led to significant changes in marketing. Companies are now making serious efforts to integrate social media into their marketing strategies. In order to be successful in these efforts, marketing experts need to think strategically, integrate social media campaigns into their marketing plans and use the right tools in the right way. They should also evaluate the campaign performance and its effect on business performance. The aim of this study is to define the strategic approach adopted by the companies and to explore how companies structure and measure their campaigns. Within the scope of the study, first literature review is made and then 20 successful Facebook campaigns are selected and analyzed through content analysis. The result of the analysis show that companies studied used megaphone strategy (by informing consumers through pages, ads and videos) and magnet strategy (by creating an environment for interaction through applications, surveys and competitions), but they did not use monitor strategy (following customers interaction with one another). Regarding how the campaigns were structured, it is found that half of them aimed to give new information and 20% were supported in offline platforms. The most preferred tool was the Facebook page, Facebook ads were more popular when compared to Facebook videos and the usage rate for surveys, competitions and applications were low. It is also found that like rate and participation rate were the two basic criteria companies used to measure the campaign performance but as the data provided by the companies was limited, it was not possible to comment on the general strategic approach they adopted.